ẢNH HƯỞNG CỦA MẬT ĐỘ ƯƠNG NUÔI ĐẾN SỰ TĂNG TRƯỞNG, TỶ LỆ SỐNG CỦA ẤU TRÙNG BÁM BÀO NGƯ VÀNH TAI (Haliotis asinina Linaeus, 1758) - Đinh, Thị Hải Yến (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE IMPACT OF STOCKING DENSITY TO THE GROWTH AND THE SURVIVAL RATE OF ABALONE IN SPAT LARVAE STAGE (Haliotis asinina, Linaeus, 1758)In this study Abalone (Haliotis asinina) spat stage larvae were reared in three different densities: 100, 200 and 300 larvae/stick (equivalent to 1 - 5 units/ml). Food use was Navicula sp. After 30 days of experiment, the results showed that the densities of 100 and 200 spat stage larvae/stick had high growth and survival rate (no statistical difference). The length of the shell size is about 3.27 mm and 3.35 mm having the survival rate is 62.0% and 68.1%, respectively. At that time, with the density of 300 spat stage larvae/stick the length of the shell size is about 2.65 mm and the survival rate is 40.9%.